Clays, Clay Minerals and Ceramic Materials Based on Clay Minerals - Morari do Nascimento, Gustavo (IntechOpen, 2016)
This book presents the state-of-the-art results of characterization of clays, clay minerals and ceramic materials based on clay minerals. The main goal of this work is to contribute to the rationalization of some important results obtained in the open area of clays and clay materials characterization. Moreover, this book also provides a comprehensive account on polymer and biopolymer-clay nanocomposites, use of clay as adsorption materials for industrial pollutants, ceramic materials in cultural heritage and physical-chemistry aspects of clay and clay minerals aqueous dispersions. This book will be beneficial for students, teachers and researchers of many areas who are interested to expand their knowledge about clays and its derivates in the fields of Nanotechnology, Biotechnology, Environmental Science, Industrial Remediation, Cultural Heritage, etc.